The hikmah (wisdom) pedagogy, moral reasoning and critical thinking in a secondary moral education class - Hafizhah binti Zulkifli
Moral Education is a subject in schools across Malaysia for non-Muslim students with the purpose of teaching them to identify a moral problem, to make a moral decision, and to act in a morally right way. It focuses on moral feelings, moral reasoning, and moral action. The literature has shown that the common teaching methods for moral education are expository, note-taking and discussion, storytelling and more recently, small group tasks and the textbook used as a major teaching aid. The method of philosophical Inquiry (PI) termed Hikmah (Wisdom) Pedagogy has never been applied to teach Moral Education in Malaysian schools. Hence, the purpose of this study was to examine the effectiveness of the Hikmah Pedagogy in enhancing moral reasoning and critical thinking among Form Two students at a public secondary school and also to explore students' views of the pedagogy. The subjects of the study were Form Two (14-year-olds) students with one class of 27 students as the treatment group and another class of 33 students as the control group. Both groups were taught similar topics for a period of 11 weeks. The control group used passages from the textbook while the treatment group used PI texts specifically designed for the study – materials consisting of pictures and videos. This study employed a quasi-experimental design and the interview method. The Defining Issues Test (DIT2) and Ujian Kemahiran Menaakul (Test for Reasoning Skill) Centre for Teaching Thinking (UKMCTT) were the instruments used to measure moral reasoning skills and critical thinking respectively. These tests were further triangulated using qualitative data which include classroom observations and document analysis of students' homework. The results of the study showed that the Hikmah Pedagogy had helped to enhance the moral reasoning stages for the treatment group as there was an increase in the post-test means score for Maintain Norms while a decrease in the post-test means score for Personal Interest and N2 score. Furthermore, the statistical t-test on critical thinking showed a significant difference in the post-test means score with the treatment group scoring a higher mean, which suggests that Hikmah Pedagogy had improved students' critical thinking. Next, the findings from the students' homework showed that the treatment group had a positive improvement in moral reasoning level based on Kohlberg's Stages of Moral Development. About 60% of the students showed a significant improvement in their moral reasoning level from homework one to homework two while 40% showed improvement from homework two to homework three. Analysis of students' questions in class showed an improvement from lower order thinking skills (LOTs) to higher order thinking skills (HOTs) questions. Students' interviews revealed eight major themes, namely (i) steps of teaching, (ii) emotional, (iii) thinking skills, (iv) learning skills, (v) communication skills, (vi) social skills, (vii) challenges, (viii) creative approach. In conclusion, the study recommends that teachers accommodate the Hikmah Pedagogy in Moral Education classes as a new innovation in 21st-century pedagogy by reducing the content of the subject syllabus as well as train themselves to be more critical and competent in facilitation skills.